Penggunaan Parameter Bentuk Dalam Pengawalan Lengkung - Abdul Majid, Noradzimah (2004)

(untitled)
Algoritma yang sesuai bagi pengekalan bentuk lengkung sangat penting dalam rekabentuk pemodelan lengkung dalam sistem RGBK Dalam menjana bentuk lengkung, kewujudan punding dan ayunan menyebabkan bentuknya menjadi tidak licin. Kelemahan ini telah menggalakkan saintis memperkenalkan kaedah bagi mengatasi masalah tersebut. Efficient algorithms for shape preserving approximation to curves are very important in shape design and modelling in CAGD system. The design of curved shapes have always posed a problem. For example, cusps and excessive oscillation have caused the shape of a curve to vary from the one suggested data.These weaknesses have encouraged scientist to introduce ways that can control the shape of a curve.